A Large Isolated Hydatid Cyst of the Adrenal Gland: A Case Report and Review of the Literature - Fatehi Elnour Elzein; Abdullah Aljaberi; Abdullah AlFiaar; Abdullah Alghamdi (Case Reports in Endocrinology)
A 44-year-old patient presented with two-year history of (R) lumbar pain. There was a strong history of childhood animals’ contact, including dogs. A brother had multiple hydatid cysts requiring surgery. Initial ultrasound showed a large (R) adrenal mass measuring 10×9×8 cm. Subsequent CT scan confirmed a heavily calcified cyst in the (R) adrenal gland. Hormonal studies were normal. He had an uneventful course following a total adrenalectomy. Isolated adrenal hydatid is extremely rare with an incidence of less than 0.5%; however, the diagnosis should always be suspected in all patients from an endemic area presenting with an adrenal cystic mass.